LINGUISTIC ANALYZES OF WORDS DENOTING INTERJECTION IN DIFFERENT LANGUAGES. - Abdullayeva Hayothon Usmonovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Words that express emotion and command and do not grammatically connect with parts of speech are called exclamation words. Although the pronouns express emotions such as excitement and driving, there is no name for emotion and driving. While you can define interjection words as those usually used to express feeling, reaction or emotion, they do have a variety of other functions too.